2010
DOI: 10.1371/journal.pone.0014254
|View full text |Cite
|
Sign up to set email alerts
|

Alanine Aminotransferase Decreases with Age: The Rancho Bernardo Study

Abstract: BackgroundSerum alanine aminotransferase (ALT) is a marker of liver injury. The 2005 American Gastroenterology Association Future Trends Committee report states that serum ALT levels remain constant with age. This study examines the association between serum ALT and age in a community-dwelling cohort in the United States.MethodsA cross-sectional study of 2,364 (54% female) participants aged 30–93 years from the Rancho Bernardo Study cohort who attended a research clinic visit in 1984–87. Demographic, metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
61
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 47 publications
13
61
1
Order By: Relevance
“…As a covariate influencing ALT activity, the association between age and ALT activity has been described in previous studies 11-13. The impact of age on ALT fluctuation is not only present based on quantitative discrimination, but also on the diagnostic value in predicting all-cause and disease-specific mortality.…”
Section: Several Concerns That Clinicians Should Raisementioning
confidence: 85%
See 1 more Smart Citation
“…As a covariate influencing ALT activity, the association between age and ALT activity has been described in previous studies 11-13. The impact of age on ALT fluctuation is not only present based on quantitative discrimination, but also on the diagnostic value in predicting all-cause and disease-specific mortality.…”
Section: Several Concerns That Clinicians Should Raisementioning
confidence: 85%
“…Specifically, age has been shown to be associated with the ALT level in prior cross-sectional and prospective studies 11-13. Elinav et al 12 reported an inverted curve with peak ALT levels at 40-55 years in a group of Israeli participants.…”
Section: Demographic Characteristics Influence the Serum Alt Levelmentioning
confidence: 96%
“…(17) In our previous cross-sectional analysis of the Rancho Bernardo Cohort (community dwelling participants residing in Southern California), we showed that older age was associated with decreased ALT, independent of sex, alcohol use, metabolic covariates, and surrogate markers of liver function. (18) All of the prior studies, however, were cross-sectional, with the potential for survivor bias. Thus, the question still remained whether a given individual’s ALT decreases with age.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that various clinic-demographic factors, such as gender and age, body fat -its distribution pattern and serum lipid levels might interfere with the liver enzymes level in the general population [3,4].…”
Section: Introductionmentioning
confidence: 99%